The effectiveness of 0.5–0.7% tetracycline gel to reduced subgingival plaque bacteria - Ernie Maduratna Setiawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: The tetracycline was an antimicrobial agent, that a broad spectrum. In addition to the antimicrobial effects, their efficacy was also anticollagenase and removal of the smear layer on the root surface. Purpose: The aim of the study was to evaluate effectiveness tetracycline gel 0.5–0.7% to reduction subgingival plaque bacteria. Method: A laboratory experimental study was conducted to investigate the effectiveness tetracycline gel 0.5–0.7%. Samples were divided into 5 groups with different concentration. The antimicrobial effect was performed using spectrophotometer. The statistical test was used One-Way ANOVA with significant difference 5% and subsequently Tukey-HSD test. Result: The study showed that tetracycline gel 0.5% has the highest antimicrobial has the highest antimicrobial effect. Conclusion: Tetracycline gel with 0.5% concentration is effective in inhibiting the growth of subgingival plaque bacteria.